Development of scalable coding of encrypted images using Modified Absolute Moment Block Truncation Code - Pankiraj, Jeya Bright; Govindaraj, Vishnuvarthanan; Zhang, Yudong; Murugan, Pallikonda Rajasekaran; Kottaimalai, R.; Jain, Paras; Thiagarajan, Arunprasath (Signal, image and video processing, 2024)
Many researchers have worked on scalable coding for unencrypted images, and there is more space for research in scalable coding for encrypted images. This paper exposits a new method of scalable coding for encrypted images, especially for lossy compression images, using the Modified Absolute Moment Block Truncation Code (MAMBTC) technique. The given input image is compressed using MAMBTC and then encrypted using a Pseudo-Random Number (PRNG) at the encryption phase. The PRNG is shared between the encoder and the decoder. At the decryption phase, the compressed pixel value is obtained by decryption using the PRNG and then reconstructed using MAMBTC, scaled by factor 2, and the Bilinear Interpolation Technique to acquire the original image. MAMBTC gives better image quality than Block Truncation Code (BTC), a higher PSNR of 36.32 dB, and a Compression ratio of 1.09, which makes the proposed system ready for signal processing applications.